2020
DOI: 10.1186/s13054-020-03090-3
|View full text |Cite
|
Sign up to set email alerts
|

Preventive use of respiratory support after scheduled extubation in critically ill medical patients—a network meta-analysis of randomized controlled trials

Abstract: Background: Respiratory support has been increasingly used after extubation for the prevention of re-intubation and improvement of prognosis in critically ill medical patients. However, the optimal respiratory support method is still under debate. This network meta-analysis (NMA) aims to evaluate the comparative effectiveness of various respiratory support methods used for preventive purposes after scheduled extubation in critically ill medical patients. Methods: A systematic database search was performed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 52 publications
(146 reference statements)
0
10
1
Order By: Relevance
“…The reason for that discrepancy was explained with the insufficiency of COT to guarantee satisfactory gas exchange compared to NIV or HFO therapy and NIV was proposed to prevent reintubation and to decrease mortality rate after planned weaning as a prophylactic approach. In our study, the HFO group had the lowest reintubation and 30-day mortality rates in contrast to the Zhou et al [9] study in which NIV was found superior to HFO regarding survival benefit but not reintubation rates. This difference was explained with higher positive airway pressure and greater improvement in cardiac performance provided by the NIV technique.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…The reason for that discrepancy was explained with the insufficiency of COT to guarantee satisfactory gas exchange compared to NIV or HFO therapy and NIV was proposed to prevent reintubation and to decrease mortality rate after planned weaning as a prophylactic approach. In our study, the HFO group had the lowest reintubation and 30-day mortality rates in contrast to the Zhou et al [9] study in which NIV was found superior to HFO regarding survival benefit but not reintubation rates. This difference was explained with higher positive airway pressure and greater improvement in cardiac performance provided by the NIV technique.…”
Section: Discussioncontrasting
confidence: 89%
“…Over the last two decades, NIV and later HFO have gained popularity in different clinical settings including weaning failure and they might increase end-expiratory lung volume and reduce work of breathing in principle but to what extent these benefits help to avoid the risk of weaning failure is unclear and unconvincing for some researchers especially in terms of high-risk patients [2,8,9] . The primary objective of this study was to prove if NIV or HFO is beneficial in decreasing weaning failure in high-risk patient population.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al recently reported a systematic review using NMA that compared NPPV, HFNC, and COT in post-extubation patients [49], but their inclusion criteria differ from ours. Zhou et al included all studies with COPD patients, whereas we excluded studies with >50% COPD patients.…”
Section: Discussionmentioning
confidence: 83%
“…Zhou et al recently reported a systematic review using NMA that compared NPPV, HFNC, and COT in post-extubation patients [ 49 ], but their inclusion criteria differ from ours. Zhou et al included all studies with patients with COPD, whereas we excluded studies with > 50% COPD patients.…”
Section: Discussionmentioning
confidence: 99%